In vivo effects of C3a on neutrophils and its contribution to inflammatory lung processes in a guinea-pig model. - Hoffmann, T (1988)
C3a, when injected intravenously in guinea-pigs, caused a rapid drop of circulating neutrophils and platelets. The neutropenia was reversible and followed by a neutrophilia, which reached about 200% of baseline values. Upon challenge with octa- and hexapeptide, mimicking the C-terminal sequence of C3a, neutrophils and platelets reacted in the same manner. The hexapeptide-desArg (pentapeptide without the C-terminal arginine of hexapeptide) induced no neutropenia but a significant neutrophilia. Likewise, when injected in animals with a genetic deficiency or dysfunction of the C3a-receptor, the hexapeptide caused no drop of the neutrophils, but a neutrophilia, indicating that both neutrophil reactions are mediated by different mechanisms. With the octapeptide in vivo dose-response studies were performed. Despite maximal doses of octapeptide about 40% of the neutrophils remained in circulation, indicating that some but not all PMNs are susceptible to C3a. By pretreating the animals with an inhibitor of the serum carboxypeptidase N (SCPN-Inh) the C3a-induced neutropenia could be significantly augmented. But intravenous application of the inhibitor itself caused a 20-40% reduction of neutrophils during the first hour after injection, followed by a neutrophilia. In histological studies the timecourse of neutrophil sequestration in the lung was established, showing that the initial high neutrophil content of the lung lasted for at least 1 h and declined thereafter. Structural derangements could not be detected. These observations stress the importance of C3a besides C5a as an important mediator of inflammatory processes in species, where the C3a-receptor is present on inflammatory cells such as granulocytes.